What Follows Tertiarisation? Structural Change and the Role of Knowledge-based Services - Michael Peneder; Serguei Kaniovski; Bernhard Dachs (Austrian Institute of Economic Research (WIFO), 2001)
The rise of the service economy has been the predominant pattern of structural change in the twentieth century. This article investigates the driving forces behind the recent stages of this development. Focusing on international input - output data from the early 1970s to the 1990s, a decomposition analysis separates the quantitative impacts of demand, technology and trade-driven determinants of output growth. Our findings confirm the rise of knowledge-based services as the most dynamic component, thus strengthening the case for "quaternarisation" as a process which is distinctly characterised by the substantial contribution of technological and organisational change to structural development.
Keywords: 330; tertiarisation; quaternarisation; knowledge-based services; structural change; input-output analysis; Strukturwandel; Wissensgesellschaft; Dienstleistungsgesellschaft; Input-Output-Analyse; Theorie